DECODING THE COMPLEXITIES OF ADVERTISING SERVICES UNDER INDIA GST REGIME: A COMPREHENSIVE GUIDE - Pushpendra Kumar; Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The introduction of the Goods and Services Tax (‘GST’) in India significantly impacted the advertising industry, necessitating a thorough understanding of its implications. This article delved into the intricacies of advertising services under the GST regime, covering various types of advertising, regulatory considerations, and challenges faced by industry players. The article began by outlining the diverse landscape of advertising services, including traditional and digital mediums, and the involvement of industry constituents such as media agencies and intermediaries. It then traced the taxability of advertising services under both the previous Service Tax Law and the current GST Law, highlighting the transition and implications for businesses. Further, the article explored the complexities surrounding advertising arrangements involving advertising agencies, distinguishing between transactions conducted in the principal’s capacity and the agent’s capacity. It discussed the nuances of GST compliance, including registration requirements, input tax credit, and the reverse charge mechanism. The article also addressed the critical aspect of determining the place of supply for advertising services, crucial for tax jurisdiction and compliance. Case studies were presented to illustrate the practical challenges and implications of GST on advertising transactions. Despite challenges such as complexity in determining the place of supply and compliance burden, the article highlighted the positive outlook for the advertising sector under GST. As businesses adapted and leveraged technology for compliance, GST was expected to bring transparency and efficiency to India’s advertising ecosystem.